Periorbital necrotizing fasciitis in a case of lid and conjunctival amyloidosis - Das, Anamika D.; Gore, Aalok S.; Vasava, Indravadan G.; Yadav, Anurag S. (International Journal of Research in Medical Sciences, 2020)
Necrotizing fasciitis is a severe, progressive, rapidly spreading infection of the subcutaneous soft tissue and underlying fascia. Periorbital necrotizing fasciitis is rare owing to the excellent blood supply of the area. Ocular amyloidosis is relatively uncommon- that of the eyelid is typically associated with systemic associations whereas amyloidosis of the conjunctiva is often localised with no other associations. Authors report a case of a 40-year-old female with a 4-year history of eyelid and conjunctival amyloidosis who presented with necrotic ulcers and eschars in the upper and lower lid with purulent discharge, conjunctival mass and a dry looking cornea in the left eye. She was a known case of rheumatoid arthritis (RA) on treatment in the last 2 years. The presentation, investigations and management are described.